Determinants of Financial Inclusion in India: A Literature Review - Kavita; Suman (Indian Journal of Finance, 2019)
Although India has achieved remarkable success in financial systems, but few segments of the Indian population, mostly poor and rural people, could not get benefit from this success due to various constraints. Financial institutions are not accessible by such a disadvantaged stratum of the population, and thereby, they are not able to participate in banking, borrowings, and savings. Providing timely and affordable financial services to entire segments of the society are termed as financial inclusion. In the present paper, various key determinants of financial inclusion such as financial literacy, institutional factors, psychological factors, technological factors, government schemes like Pradhan Mantri Jan Dhan Yojna, self-help groups, and microfinance, etc. were discussed on the basis of existing theoretical and empirical literature on financial inclusion. Each determinant of financial inclusion has its own importance in realizing the objective of complete and comprehensive financial inclusion in India.